Exploiting Vulnerabilities of HB-MP - Carrijo, José; Tonicelli, Rafael (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2009)
HB-MP is a prominent member of the HB-family: a family of authentication protocols specially designed for RFID tags. We present two different cryptanalytic methods on HB-MP: (1) a passive attack based solely on the eavesdropping of legitimate authentication procedures; (2) an active attack, where the adversary has control over the RFID tag and is allowed to change the content of chosen memory areas of the device.